Bridging the Financial Divide: Factors That Influence Financial Exclusion amongst The Unbanked Population of Botswana - Seleka, Gaone Geoffrey (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The aim of this research is to determine the primary causes behind the unbanked population's exclusion from Botswana's official financial system. The study aims to address the following research question: What are the main causes of the unbanked population's exclusion from Botswana's formal financial system, and how do these causes affect financial inclusion? Deign/Methodology/Approach: This study used a mixed-methods approach to research, collecting and analysing data using both quantitative and qualitative techniques. Participants in the data collection process were given surveys to accomplish this goal. These surveys collected detailed data regarding people's financial inclusion status in Botswana. The surveys also explored the reasons behind the unbanked population's absence from the official financial system. Findings: The study's findings indicate that the unbanked population's degree of financial inclusion in Botswana is greatly impacted by the factors that keep them out of the country's formal financial system. The results of this study will add to the body of knowledge in business studies and financial technologies. Additionally, Mobile Network Operators (MNOs), commercial banks, government policy makers, and regulators in the financial and insurance sectors can use the study's findings to obtain useful information and guidance.